Solvability of a Doubly Singular Boundary Value Problem Arising in Front Propagation for Reaction-Diffusion Equations (Contemporary Mathematics, 2024)
The paper deals with the solvability of the following doubly singular boundary value problemnaturally arising in the study of the existence and properties of travelling waves for reaction-diffusion-convection equationsgoverned by the p-Laplacian operator. Here c, α are real parameters, with α > 0, and f, g, h are continuous functions in [0, 1], withh(0) = h(1), h(u) > 0 in (0, 1).
Keywords: singular boudary value problems; reaction-diffusion-convection equations; travelling wave solutions; degenerate parabolic equations; speed of propagation